Welding Structures in Gas Tungsten Arc-Welded Zircaloy-4 - Perez, Teresa Estela; Saggese, María Eugenia (North Holland Publishing Company, 1982)
Fil: Perez, Teresa Estela Comisión Nacional de Energía Atómica; Argentina